Acompanhamento farmacoterapêutico de pacientes ambulatoriais com artrite reumatoide: desenvolvimento e avaliação - Oliveira, Bruna Esmeraldo (2023)
Objectives: The study aimed to develop a pharmacotherapeutic follow-up (PF) service model for outpatients with rheumatoid arthritis (RA) in a teaching hospital; evaluate PF through process and result quality indicators; and validate the Compliance Questionnaire Rheumatology (CQR) instrument for the Portuguese language. Methods: The research consisted of a descriptive, longitudinal, prospective and intervention study, which developed and evaluated a PF model, and a methodological study of construct validation and reliability of the CQR for the Portuguese language, which were carried out at the Outpatient Pharmacy and the Rheumatology Outpatient Clinic of the Walter Cantídio University Hospital. The PF model was based on the Dáder clinical method and presented the stages of service offering, initial pharmaceutical consultation, pharmacotherapy review, intervention and feedback. The PF evaluation was guided by implementation indicators: process (feasibility, fidelity, acceptability and relevance); clinical results (pharmacotherapy problems, pharmaceutical interventions, inflammatory activity and cardiovascular risk); and humanistic results (adherence to treatment, functional capacity, quality of life and satisfaction with PF). The CQR validation and reliability process included: cross-cultural adaptation, structural validation by factor analysis and internal consistency evaluation. Composite reliability was also evaluated. Results: The PF retention-participation rate was 77.8% and fidelity was 90%, with 87.4% of consultations performed. 91.6% of identified pharmacotherapy problems were resolved by the acceptability of 95% and 77% of pharmaceutical interventions by patients and physicians, respectively. The cross-cultural adaptation produced the brazilian version of the CQR (bCQR), whose factor analysis identified a unidimensional structure, with good data fit after confirmatory factor analysis (not significant x 2 ; p=0.788), adequate results when tested in different fit models and maintenance of 19 items, according to factor loads. Cronbach's alpha coefficient (0.75) and composite reliability (0.84) indicated a strong factorial structure and reliability of the bCQR. Conclusion: The development and evaluation of the outpatient PF model, based on systematic planning, showed the potential for implementation and institutionalization this service, which can contribute to improving the quality of health services involved in the formation of the scientific and educational skills of the pharmacist and expanding their role in clinical practice. Validation of the bCQR produced a reliable instrument for assessing adherence in patients with RA, which may be useful in research and clinical practice, as a screening tool, or to guide educational interventions.